2015
DOI: 10.1186/s13293-015-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in substance use, health, and social functioning among opioid users receiving methadone treatment: a multicenter cohort study

Abstract: BackgroundDespite the growing numbers of men and women with opioid use disorder in Canada, sex-specific issues in treatment have not been re-examined in the current population of patients with opioid addiction. We aimed to evaluate sex differences in substance use, health, and social functioning among men and women currently receiving methadone treatment for opioid use disorder in Ontario, Canada.MethodsWe recruited 503 participants with opioid dependence disorder receiving methadone maintenance treatment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 46 publications
10
63
3
1
Order By: Relevance
“…Ethics approval was obtained from the Hamilton Integrated Research Ethics Board (project ID 11-056), and written informed consent was obtained from each study participant. Further details related to GENOA study methods have been previously reported 3134. This study is reported in accordance with the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines 35…”
Section: Methodsmentioning
confidence: 85%
“…Ethics approval was obtained from the Hamilton Integrated Research Ethics Board (project ID 11-056), and written informed consent was obtained from each study participant. Further details related to GENOA study methods have been previously reported 3134. This study is reported in accordance with the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines 35…”
Section: Methodsmentioning
confidence: 85%
“…Women in MMT tend to show a higher prevalence of comorbid psychiatric and physical illnesses [16, 43, 44], as well as more severe opioid craving upon treatment entry [45] which may represent confounding factors that serve to increase rates of both cannabis and opioid use during MMT. As such, these patients may have motivation to use both drugs for purposes of self-medication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies point to a changing landscape of OUD and those in treatment, one that includes a higher percentage of women, older aged patients, and more individuals abusing prescription opioids rather than heroin [16]. These sociodemographic changes warrant a re-evaluation of risk factors associated with poor MMT outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found women compared with men were more likely to have a family history of mental illness and to initiate opioid use through a physician. Alternatively, men were found to have higher rates of cigarette smoking and cannabis use compared to women (12). The other clinic based study used a cross-sectional method to interview 162 participants as part of a 7-week inpatient and 12-week outpatient study.…”
Section: Introductionmentioning
confidence: 99%